1971
DOI: 10.1126/science.173.4003.1248
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Evoked Potentials during Speech Perception

Abstract: Neural responses evoked by the same binaural speech signal were recorded from ten right-handed subjects during two auditory identification tasks. One task required analysis of acoustic parameters important for making a linguistic distinction, while the other task required analysis of an acoustic parameter which provides no linguistic information at the phoneme level. In the time interval between stimulus onset and the subjects' identification responses, evoked potentials from the two tasks were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
40
0

Year Published

1974
1974
1987
1987

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(52 citation statements)
references
References 33 publications
12
40
0
Order By: Relevance
“…This unidirectional or asymmetric interference between linguistic and nonlinguistic dimensions is consistent with other data that distinguish between auditory and phonetic levels of processing in speech perception (for a recent review, see Studdert-Kennedy, in press). As is the case in a number of other experimental paradigms (e.g.. Day & Bartlett, 1972;Day, Cutting, & Copeland, 1971;Wood, 19.15;Wood, Goff, & Day, 1971), the linguistic status of a dimension may be an important factor in speeded classification experiments.…”
Section: Linguistic and Nonlinguistic Dimensionsmentioning
confidence: 93%
“…This unidirectional or asymmetric interference between linguistic and nonlinguistic dimensions is consistent with other data that distinguish between auditory and phonetic levels of processing in speech perception (for a recent review, see Studdert-Kennedy, in press). As is the case in a number of other experimental paradigms (e.g.. Day & Bartlett, 1972;Day, Cutting, & Copeland, 1971;Wood, 19.15;Wood, Goff, & Day, 1971), the linguistic status of a dimension may be an important factor in speeded classification experiments.…”
Section: Linguistic and Nonlinguistic Dimensionsmentioning
confidence: 93%
“…A number of researchers have shown that speech signals are better perceived by the left hemisphere (right ear) whereas nonspeech signals are better processed by the right hemisphere (left ear) (Kimura, 1961(Kimura, , 1964Studdert-Kennedy &, Shankweiler, 1970). Electrophysiological studies of neural activity have also, supported this conclusion in adults (Wood, Goff, & Day, 1971).…”
mentioning
confidence: 94%
“…Sperry, 1968). Wood, Goff and Day (1971) report that AEPs from the left hemisphere differed when linguistic information was presented, as compared to when nonlinguistic patterns of the same acoustic signal were presented. The right hemisphere AEPs were the same for linguistic and nonlinguistic auditory stimuli.…”
Section: IIImentioning
confidence: 99%